HUBUNGAN ANTARA KOMPETENSI GURU DENGAN KEMAMPUAN GURU PAI DALAM INOVASI DAN EVALUASI PEMBELAJARAN PAI DI MADRASAH IBTIDAIYAH DI ACEH TAMIANG - Eva Sari Wati Tampubolon; Samsul Susilawati; Alfin Mustikawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The main problem of this study is the suboptimal role of Islamic Religious Education (PAI) teachers in innovating and conducting comprehensive learning evaluations. Although PAI teachers bear a major responsibility in shaping students’ character and morals, there are still limitations in implementing innovative teaching methods and carrying out effective evaluations. This highlights the need to examine the extent to which teachers’ competencies: covering pedagogical, personal, social, and professional aspects are related to their ability to innovate and evaluate learning. The aim of this study is to analyse the relationship between teachers’ competence and the ability of PAI teachers to innovate, as well as the relationship between teachers’ competence and their ability to conduct learning evaluations in Islamic Primary Schools (Madrasah Ibtidaiyah) in Aceh Tamiang Regency. This research employs a quantitative approach with a correlational design. The population consists of all PAI teachers in the Islamic primary schools within the regency, using a total sampling technique so that all teachers serve as respondents. Data were collected through questionnaires, interviews, and documentation, and the instruments were tested for validity and reliability. Data analysis utilised Pearson’s Product Moment correlation and simple linear regression analysis. The findings show a positive and significant relationship between teachers’ competence and their ability to innovate, as well as between teachers’ competence and their ability to conduct learning evaluations in PAI. The higher the teachers’ competence, the greater their ability to implement effective and sustainable innovation and evaluation in PAI teaching.